Impact of radial migration on stellar and gas radial metallicity distribution. Issue 4 (29th January 2015) - Grand, Robert J. J.; Kawata, Daisuke; Cropper, Mark
Abstract : Radial migration is defined as the change in guiding centre radius of stars and gas caused by gains or losses of angular momentum that result from gravitational interaction with non-axisymmetric structure. This has been shown to have significant impact on the metallicity distribution in galactic discs, and therefore affects the interpretation of Galactic archaeology. We use a simulation of a Milky Way-sized galaxy to examine the effect of radial migration on the star and gas radial metallicity distribution. We find that both the star and gas component show significant radial migration. The stellar radial metallicity gradient remains almost unchanged but the radial metallicity distribution of the stars is broadened to produce a greater dispersion at all radii. However, the metallicity dispersion of the gas remains narrow. We find that the main drivers of the gas metallicity distribution evolution are metal enrichment and mixing: more efficient metal enrichment in the inner region maintains a negative slope in the radial metallicity distribution, and the metal mixing ensures the tight relationship of the gas metallicity with the radius. The metallicity distribution function reproduces the trend in the age–metallicity relation found from observations for stars younger than 1.0 Gyr in the Milky Way.